2006
DOI: 10.1007/s00542-006-0295-8
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of spreading characteristics of molecularly thin lubricant films over grooved solid surfaces based on diffraction simulations

Abstract: Characteristics of molecularly thin lubricant films are basically determined by their interactions with solid surfaces. Since these interactions can be modified by engineered microscopic surface textures, it is expected that rational design of the textures will make it possible to attain desired tribological functions and performance. In this research, with the aim of applying it to head-disk interface of hard disk drives, we propose a method based on diffraction simulations that enables thickness measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…From Figure b, we observe that the polymer typically spreads much less perpendicular to the texture than parallel to the texture, in agreement with previous reports. ,, Similar to the case of Figure a, we observe that textures with the same aspect ratio can yield different d ⊥ . Thus, the texture aspect ratio does not necessarily determine anisotropic spreading d || / d ⊥ , in opposition to previous reports. , We also observe that d ⊥ decreases with decreasing L and that this is more pronounced for textures with sharp grooves, especially grooves with θ = 60°.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…From Figure b, we observe that the polymer typically spreads much less perpendicular to the texture than parallel to the texture, in agreement with previous reports. ,, Similar to the case of Figure a, we observe that textures with the same aspect ratio can yield different d ⊥ . Thus, the texture aspect ratio does not necessarily determine anisotropic spreading d || / d ⊥ , in opposition to previous reports. , We also observe that d ⊥ decreases with decreasing L and that this is more pronounced for textures with sharp grooves, especially grooves with θ = 60°.…”
Section: Resultssupporting
confidence: 91%
“…The ability to create anisotropic spreading in particular, which enables liquid spreading to occur in a user-specified direction, finds application in micro/nanofluidics, flexible electronics, and drag reduction surfaces . Several research groups have shown both experimentally and numerically that unidirectionally textured substrates lead to anisotropic spreading, where liquids spread preferentially in the direction parallel to the texture. Anisotropic spreading on unidirectionally textured substrates is most commonly explained by texture peaks, which impose a mechanical barrier that effectively “pins” the three-phase (solid/liquid/gas) contact line of the spreading liquid, inhibiting spreading in the direction perpendicular to the texture. , The texture peaks are often described as energetic barriers that oppose wetting, which Yong and Zhang attribute to a high local atomic density at texture peaks, based on the results of molecular dynamics (MD) simulations (texture height of 1.85-23.77 Å). The liquid may be confined by texture peaks in the perpendicular direction and “squeezed” in the parallel direction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation